+0  
 
0
74
2
avatar+524 

The value of  \(3[sin^4({3\pi \over 2}-a)+sin^4(3\pi+a)] - 2[sin^6({\pi \over 2}+a)+sin^6(5\pi-a)]\)  is 

 

Thank you. 

 Jun 15, 2021
 #1
avatar+121006 
+2

sin  (3pi/2  - a)  =    sin(3pi/2)cosa  + cos(3pi/2)sina  =  -cosa

So

sin4  ( 3pi/2  -a)  =   (-cos a)^4  =   (cos a)^4

 

sin ( 3pi  + a)   =   sin (3pi) cos a   -  cos(3pi)sina   =   sina

So

sin 4 ( 3pi  + a)   =  ( sin a)^4

 

sin ( pi/2 + a)  =  sin (pi/2)cos a   -  sin a cos (pi/2)   =  cos a

So

sin 6  (pi/2  + a)    =   (cos a)^6

 

sin (5pi  -a)  =  sin (5pi)cosa   + sin a cos (5pi)  =  -sina

So

sin 6 ( 5pi -a)   =  (-sin a)^6  =   (sin a)^6

 

 

So

 

3   [  (cos a)^4   +  (sin a)^4  ]  -  2  [ (cos a)^6  + (sin a)^6  ]   =

 

Special  identites

 

cos ^4 a    =    (3 + 4cos (2a) + cos (4a))  / 8

sin^4  a   =     (3  - 4cos (2a)  + cos (4a) )  / 8

 

So.....the first expression   evaluates  to

 

(3/8)  ( 6  + 2cos (4a) )  = 

(9/4) + (3/4)cos(4a)

 

Also

cos^6 a   =  (1/32)  ( 15cos (2a) + 6cos (4a) + cos (6a) + 10 )

sin ^6 a    = (1/32)   (-15cos (2a)  + 6cos (4a)   - cos (6a) + 10 )

 

So......the  second expression  evaluates  to  

 

-(2/32)   ( 12cos (4a)  +  20)  =

-(1/16)   ( 12cos (4a) +   20)  =

-(3/4)cos (4a)  -  5/4

 

So

 

[ (9/4)  + (3/4)cos (4a)  ]  -  [ (3/4)cos (4a)  + 5/4)  ]   =

 

9/4    -  5/4   =

 

4/4    = 

 

1

 

 

cool cool cool

 Jun 15, 2021
 #2
avatar+524 
+2

Thanks a lot! laugh

amygdaleon305  Jun 16, 2021

11 Online Users

avatar